2000
DOI: 10.1021/ja001471o
|View full text |Cite
|
Sign up to set email alerts
|

Aren-BuLi/TMEDA-Mediated Arene Ortholithiations Directed? Substituent-Dependent Rates, Substituent-Independent Mechanisms

Abstract: Rate studies of the lithiation of benzene and related alkoxy-substituted aromatics by n-BuLi/TMEDA mixtures implicate similar mechanisms in which the proton transfers are rate limiting with transition structures of stoichiometry [(n-BuLi)2(TMEDA)2(Ar−H)]⧧ (Ar−H = benzene, C6H5OCH3, m-C6H4(OCH3)2, C6H5OCH2OCH3, and C6H5OCH2CH2N(CH3)2). Cooperative substituent effects and an apparent importance of inductive effects suggest a mechanism in which alkoxy−lithium interactions are minor or nonexistent in the rate-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 53 publications
1
60
1
4
Order By: Relevance
“…Of immense importance is the lithiation of arenes by means of the so-called directed ortho metalation (DoM) method [2]. Since the pioneering work of Gilman [5], several methodologies have been developed to synthesize aryllithium compounds [6][7][8][9][10][11][12][13][14], namely halogen-lithium exchange [11,15], directed lithiation [16][17][18][19][20][21] and direct deprotonation processes [17,[21][22][23]. It should be noted that the lithiation of unsubstituted arenes is normally a very slow process.…”
Section: Introductionmentioning
confidence: 99%
“…Of immense importance is the lithiation of arenes by means of the so-called directed ortho metalation (DoM) method [2]. Since the pioneering work of Gilman [5], several methodologies have been developed to synthesize aryllithium compounds [6][7][8][9][10][11][12][13][14], namely halogen-lithium exchange [11,15], directed lithiation [16][17][18][19][20][21] and direct deprotonation processes [17,[21][22][23]. It should be noted that the lithiation of unsubstituted arenes is normally a very slow process.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that inductive effects are of great importance and precomplexation between lithium and a substituent is not a factor in this DoM. [58] 2.7. Deprotonative Lithiations: CIPE or "Kinetically Enhanced Metalation"?…”
Section: Are Calculations Indicative Of Cipe?mentioning
confidence: 95%
“…[58] The fact that these reactions follow a common rate law was interpreted to favor a triple-ion model consistent with a lack of oxygenlithium complexation in the transition state for the ratelimiting proton transfer. This hypothesis is consistent with ab initio calculations (see Section 2.6).…”
Section: Mechanism Of Lithiationmentioning
confidence: 99%
“…Pendant amides and carbamates effectively direct lithiation of arenes 32 and alkanes, 1 including cyclopropanes. 33,34 The enhanced acidity of the deprotonated hydrogen in these cases is attributed variously to dipole-stabilization 1,35 and the complexinduced proximity effect. 36 For the sake of computational economy, deprotonation of trans-␤-formylcyclopropylnitrile 5c was examined (Fig.…”
Section: Chiral Lithiated Cyclopropylnitrilesmentioning
confidence: 99%